Brief executive-function assessment tool: A new cognitive impairment screening tool for alcohol and other drug services. Issue 6 (2nd November 2022) - Berry, J.; Shores, E. A.; Nardo, T.; Sedwell, A.; Lunn, J.; Marceau, E. M.; Wesseling, A.; Zucco, M.; Sugden-Lingard, S.; Borchard, T.; Batchelor, J.
Abstract: Accurate screening for cognitive impairment in alcohol and other drug (AOD) services would help to identify individuals who may need supports to obtain the greatest benefit from substance use disorder (SUD) treatment. At present there is no screening measure that has been developed specifically to detect cognitive impairment in a SUD population. This study examines the psychometric properties of the Brief Executive-function Assessment Tool (BEAT), which was specifically designed for this purpose. This study involving 501 individuals with SUD and 145 normal control participants established internal consistency ( n = 646; 0.734), interrater ( n = 60; 0.994), and test–retest reliability ( n = 177; 0.845), and construct (all correlations p ≤ 0.05), and criterion ( n = 467; ANCOVA p < 0.001) validity. Test operating characteristics ( n = 500; 87% sensitivity, 71% specificity, 21% PPP, and 99% NPP ) were also established relative to an independent criterion variable made up of three established performance-based neuropsychological tests. Findings support the reliability and validity of the BEAT as a screening measure of executive function impairment with high sensitivity and a low rate of false negatives.